A quantitative analysis of ground contact time, impulse, and average force in various plyometric exercises - Carroll, C.; Mehlhorn, J. D.; Treimer, J. (Journal of Athletic Enhancement, 2017)
Objective: Hurdle hops and jumping variations have been utilized as explosive, reactive movements by strength coaches to prepare their athletes and optimize their rate of force production. The purpose of this study was to analyze the differences in ground contact time and impulse between hurdle hops and two separate jump variations. The objective is to provide sports performance professionals with a quantitative analysis of these movements to enhance the quality and overall effectiveness of their training regimens.